Collision characteristics of shoulder charge tackles in elite rugby league - Cummins, C.; Orr, R. (International Journal of Performance Analysis in Sport, 2015)
The study objective was to investigate the tackle and collision characteristics of shoulder charge tackles within elite rugby league match-play. Tackle characteristics and injury outcomes from video footage of 201 matches (30 NRL rounds and finals series) were examined. Players were categorised into positional groups: hit-up forwards, adjustables and outside backs. Where possible, data from Global Positioning System (GPS) units worn by players were linked to video footage for analysis. Tackles were classified as shoulder charge or conventional tackle. Outcome measures included shoulder charge incidence, tackle characteristics and impacts (G-force) sustained during shoulder charge tackles. In 201 video files, 59 shoulder charges were identified from 123,211 tackles. Shoulder charge incidence was 0.05% of total tackles, with an average rate of 0.29 shoulder charges per game. However, shoulder charge incidence increased from 0.22 in rounds 1-26 to 1.88 in the final series. In the majority of shoulder charge tackles (P=0.000) players executed the tackle through transferring body mass over the front foot and driving the right shoulder in an upright and oblique approach to the ball carrier. Impact forces from GPS ranged from 6.5-13.4G and 7.9-12.3G for attackers and defenders, respectively. The physical demands of the tackle were within the highest classification of sustained impacts during match-play.